Philosophical and theological writings - Lessing, Gotthold Ephraim, 1729-1781 (Cambridge texts in the history of philosophy., 2005)
This volume presents the most comprehensive collection to date in English of Lessing's philosophical and theological writings, several of which appear here in English for the first time. They are translated and edited by H.B. Nisbet, who also provides an introduction that sets them in their historical and philosophical contexts.